2015
DOI: 10.18203/2349-2902.isj20150400
|View full text |Cite
|
Sign up to set email alerts
|

Lateral transdeltoid approach to proximal humerus fractures

Abstract: INTRODUCTIONFractures of the proximal humerus are the most common fractures of this bone and constitute 5-6% of the total fracture incidence in adults; and this incidence increases with age.1 Complex fractures of the proximal humerus are often difficult to treat and result in considerable shoulder dysfunction unless adequately treated.2 According to the Neer's criteria for the proximal humerus fractures, fractures with fragments separated more than 1 cm or with more than 45 degree angulation are considered as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…However, in some cases, LDSA may be preferred due to characteristics of the pathology and necessity of extended approach. The main complication of the LDSA is iatrogenic axillary nerve injury [11]. In this study, we evaluated the patients who were operated for proximal humerus fracture with LDSA with regards to axillary nerve integrity and shoulder functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some cases, LDSA may be preferred due to characteristics of the pathology and necessity of extended approach. The main complication of the LDSA is iatrogenic axillary nerve injury [11]. In this study, we evaluated the patients who were operated for proximal humerus fracture with LDSA with regards to axillary nerve integrity and shoulder functions.…”
Section: Discussionmentioning
confidence: 99%
“…Altı ay sonra tüm hastaların opere edilen ve edilmeyen omuzları elektrofizyolojik testler (Elektronöromiyelografi -ENMG) ve Constant Omuz Skoru (CSS) ile karşılaştırmalı olarak değerlendirildi. Opere edilen ve edilmeyen omuzların CSS farkları hafif (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), orta (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), şiddetli (>30) olarak derecelendirildi. Bulgular: Hastaların yaş ortalaması 66(9) idi.…”
Section: öZunclassified
“…The functional outcome of direct lateral approach for fixation of proximal humeral fractures: A case series from a tertiary care hospital Mujahid Jamil Khattak, 1 Irfan Anwer, 2 Muhammed Tabish Saleem, 3 Ahmed Abdul Habib Khan, 4 Mohammad Zohaib Nawaz Khan 5 presenting with neurological deficit or associated shoulder dislocation at the time of presentation were excluded. Ethical approval from institutional Review Committee was obtained before commencement of our study.…”
Section: Case Seriesmentioning
confidence: 99%
“…Recently, Singh et al, however reported no incidence of nerve damage in a retrospective review of patients who underwent fixation by the lateral transdeltoid approach. 3 Liu et al 4 also found trans deltoid approach to be the better alternative in patients due to better function and range of motion achieved with this approach.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation